2011
DOI: 10.1088/0953-8984/23/22/225402
|View full text |Cite
|
Sign up to set email alerts
|

The re-entrant phase transitions in crystalline malononitrile, CH2(CN)2: a neutron powder diffraction study

Abstract: The temperature dependence of the crystal structures of the low-temperature α-phase and the intermediate-temperature β-phase of crystalline malononitrile, CH(2)(CN)(2), have been determined using Rietveld refinement on neutron powder diffraction data. The results confirm that the α-phase has the same structure as the high-temperature γ-phase, and the refined structure of the β-phase is in agreement with previous structure determination using single-crystal x-ray diffraction. The variations of the structure wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 27 publications
(66 reference statements)
0
14
0
Order By: Relevance
“…The Rochelle salt, NaKC 4 H 4 O 6 ·4H 2 O, crystallizes in the space group P 2 1 2 1 2 above 297 K and below 255 K, but exists in a distorted ferroelectric intermediate phase (space group P 2 1 11) in the temperature region of 255–297 K . Other well documented examples include malonitrile, CH 2 (CN) 2 and hybrid-layered perovskites (C 3 H 7 NH 3 ) 2 MnCI 4 . Examples of purely inorganic materials are even more rare; to our knowledge, the ionic conductor Ag 7 P 3 S 11 and the rock-salt Li 2 TiO 3 are the only known examples.…”
Section: Introductionmentioning
confidence: 99%
“…The Rochelle salt, NaKC 4 H 4 O 6 ·4H 2 O, crystallizes in the space group P 2 1 2 1 2 above 297 K and below 255 K, but exists in a distorted ferroelectric intermediate phase (space group P 2 1 11) in the temperature region of 255–297 K . Other well documented examples include malonitrile, CH 2 (CN) 2 and hybrid-layered perovskites (C 3 H 7 NH 3 ) 2 MnCI 4 . Examples of purely inorganic materials are even more rare; to our knowledge, the ionic conductor Ag 7 P 3 S 11 and the rock-salt Li 2 TiO 3 are the only known examples.…”
Section: Introductionmentioning
confidence: 99%
“…Purely structural re-entrant phase transitions in crystalline materials are very rare. A recent study suggests only three known examples 21 ; this has now been supplemented by one further possible case 22 . Interestingly, in the latter case, the transformation has the same group-subgroup relationship (R-3 to P-1) as presented here, though it is suggested that the transition is due to competition between a weak Jahn-Teller effect and magnetic ordering; in our case the cause is more likely to be purely structural and related to the fluorine disorder.…”
mentioning
confidence: 99%
“…The tube was then heated under flowing argon at 10 uC min 21 to 600 uC for twelve hours before cooling at the same rate. In the case of single crystals the molar ratio was adjusted to 3 : 2 : 3 (in order to provide a flux for crystal growth), the temperature increased to 800 uC and the cooling rate slowed to y3 uC h 21 . In all cases it was very difficult to synthesise the pure Rb 2 SnCu 3 F 12 phase, with significant impurities being Rb 2 SnF 6 and CuO.…”
mentioning
confidence: 99%
“…The observation of such complex phase behaviour has been attributed to the fact that high-pressure forces electron density to order in less conventional ways to accommodate the pressure-induced reduction in volume, and hence minimize the impact of the pV contribution to the enthalpy of the system. A limited number of other elemental metals (Porsch & Holzapfel, 1993), as well as peroskites and pure inorganics (Kabbour et al, 2012;Downie et al, 2013;Brinkmann et al, 2004), have been show to display pressure-induced re-entrant phase behaviour, defined by Dove as a transition where there is a sequence of two phase transitions, with the first and third phases having the same symmetry and effectively identical structures (Dove, 2011). In molecular solids, such transitions are exceptionally rare, with only two well-known purely structural examples, namely rochelle salt and malonitrile (Levitskii et al, 2010;Beevers & Hughes, 1941;Suzuki & Shiozaki, 1996;David et al, 2013;Dove & Rae, 1983;Wasiutynski et al, 1987;Dove, 2011).…”
Section: Introductionmentioning
confidence: 99%